Ottawa Heart Institute Research Corporation (OHIRC) Technology Management Program - Alcala, Eduardo; Liddle, Stephanie; Zaktuney, Timothy (CMBES Proceedings, 2023)
The absence of a structured technology management program for research equipment in the Ottawa Heart Institute Research Corporation (OHIRC) has been a deterrent leading to decreased uptime, unrepairable equipment, low collaboration between researchers, poor long-term capital planning, and increased costs. Apart from furniture, consumables, and fixtures, there is an active fleet of approximately 1700 pieces of equipment of which a few of them are being managed through service contracts. Therefore, a new technology management program for research equipment was developed, and currently oversees the inventory, documentation, scheduled and unscheduled maintenance, initial inspection, contract management, equipment procurement, decommission, and research grant application assistance. The designed workflows, processes, and tools are aligned with pre-existing processes in the Biomedical Engineering (BME) department supporting the clinical University of Ottawa Heart Institute (UOHI). A permanent, full-time BME Technologist dedicated to research equipment has been hired to fulfill long-term program requirements. The strategy has been slowly integrated, and it is currently under analysis to identify efficiencies and fulfill researchers' needs. Through the expertise of the Biomedical and Clinical Engineering departments, this work presents a novel strategy to manage research equipment within a healthcare facility.